A simple modification in the DNA extraction process to extract good quality bacterial DNA from milk - KOUR, GURLEEN; CHANDRA, MUDIT; KAUR, GURPREET; NARANG, DEEPTI; GUPTA, D K (The Indian Journal of Animal Sciences, 2020)
Mastitis is the inflammation of the udder characterized by pathological changes in the mammary gland tissue. The most common treatment regimen involves administration of antibiotics depending upon culture and antibiotic sensitivity test. Culture and antibiotic sensitivity testing requires a minimum of 2-3 days, thus search for alternative tests to quicken identification of causative agent has gained lot of focus. In mastitis, milk is the ideal sample for the identification of causative agents as well as for performing DNA based tests such as PCR. Milk though easy to collect, harbour certain inhibitors affecting isolation of DNA. Also, the DNA extracted might contain certain associated ions which interfere in PCR. In the present study, DNA was extracted from milk by initially treating it with SDS and triton and later DNA was extracted using standard phenol chloroform method (M1). The efficiency of extraction by this method (M1) was compared with that of a kit (Power food microbial DNA isolation kit) based method (M2). The DNA extracted from both the methods was evaluated and compared among each other using genus specific PCR for E. coli, Klebsiella spp., Staphylococcus spp. and Streptococcus spp. along with various antibiotic resistance genes present in these bacteria. From the study, it could be concluded that DNA could be extracted successfully using SDS and triton method directly from the milk more efficiently and is cost effective when compared with kit-based method.